Pengaruh Pola Asuh Otoriter Orang Tua dan Kontrol Diri terhadap Perilaku Agresif Siswa - Viska Dea Nopiana; Puspa Rahayu Utami Rahman; Yulyanti Minarsih (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Aggressive behavior in adolescents is a common problem in schools because it can disrupt learning and social interactions. Factors influencing this include parental parenting styles and the individual's ability to control themselves. Therefore, it is important to understand how parental authoritarian parenting styles and self-control contribute to students' aggressive behavior. This study aims to analyze the influence of maternal authoritarian parenting styles, paternal authoritarian parenting styles, and self-control on aggressive behavior in adolescents. The study used a quantitative approach with a causality method. The sample consisted of 279 students in grades 10 and 11 of SMKN 2 Karawang. The instruments used included the Parental Authority Questionnaire (PAQ) to measure parental parenting styles, the Brief Self-Control Scale (BSCS) to measure self-control, and the Aggression Questionnaire to measure students' levels of aggressiveness. The results showed that maternal authoritarian parenting styles significantly influenced aggressive behavior, as did paternal authoritarian parenting styles and self-control. All three simultaneously had a significant influence on students' aggressive behavior. Quantitatively, authoritarian parenting styles of mothers, fathers, and self-control contributed 23.1% to aggressive behavior, while the remaining 76.9% was influenced by other factors not examined in this study. These findings emphasize the importance of appropriate parenting styles and strengthening adolescents' self-control skills to minimize aggressive behavior at school.